1993
DOI: 10.3133/ofr93235
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis and ore controls in the Coeur D'Alene mining district, Idaho

Abstract: Beltian rocks in the Coeur d' Alene district of Idaho, lying within the Lewis and Clark line, display a complex history of deformation and metamorphic fabrics. The earliest fabric is a near-bedding-parallel schistosity (assigned to Dl). Upright folds of northerly trend lie north of the district; comparable folds partly overturned trend WNW within the district, subparallel to the Osburn fault. The folds are assigned to D2a.Metamorphic cleavage (assigned to D2b) trends generally WNW but cuts across the folds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The Belt Supergroup south of the Coeur d'Alene district experienced greenschistto amphibolite-facies metamorphism that has been attributed to either Precambrian tectonism of uncertain origin (Reid and Greenwood, 1968;Reid et al, 1981, Hyndmann et al 1988 or more commonly to emplacement of the Cretaceous Idaho Batholith (e.g., Hietanen, 1984;Grover et al,1992;Lang and Rice, 1985a,b,c). Recent Lu/Hf garnet dating has demonstrated that much of the metamorphism to the south is in fact Proterozoic in age (Zirakparvar et al, 2010;Nesheim et al, 2012).…”
Section: Regional Geology Of the Coeur D'alene Districtmentioning
confidence: 99%
See 1 more Smart Citation
“…The Belt Supergroup south of the Coeur d'Alene district experienced greenschistto amphibolite-facies metamorphism that has been attributed to either Precambrian tectonism of uncertain origin (Reid and Greenwood, 1968;Reid et al, 1981, Hyndmann et al 1988 or more commonly to emplacement of the Cretaceous Idaho Batholith (e.g., Hietanen, 1984;Grover et al,1992;Lang and Rice, 1985a,b,c). Recent Lu/Hf garnet dating has demonstrated that much of the metamorphism to the south is in fact Proterozoic in age (Zirakparvar et al, 2010;Nesheim et al, 2012).…”
Section: Regional Geology Of the Coeur D'alene Districtmentioning
confidence: 99%
“…Recent Lu/Hf garnet dating has demonstrated that much of the metamorphism to the south is in fact Proterozoic in age (Zirakparvar et al, 2010;Nesheim et al, 2012). Several models for the origin of Coeur d'Alene mineralization suggest that fluids generated during low-grade greenschist facies metamorphism transported the metals to the sites of deposition (Reid and Hayden, 1993;Constantopoulos, 1994).…”
Section: Regional Geology Of the Coeur D'alene Districtmentioning
confidence: 99%